Performance of Consumer Forums: An Empirical Study of Kadapa District Consumer Forum - Sudarsana Murthy, D.; Narasaiah, P. V.; Mohan, B. (Prabandhan: Indian Journal of Management, 2013)
Majority of the consumers in India - whether rich or poor, literate or illiterate, urban or rural often become the victims of adulterated, spurious, hazardous and substandard goods as well as wrong measurements and high prices. Shortage in supply of several commodities, unethical and deceptive advertisements enable the businessmen and traders to make quick money at the cost of the consumers. Even the goods/services of State undertakings, nationalized banks, electricity and tele-communications etc., are not exceptions. Despite a number of laws to protect the interests of the consumers, the Indian consumer is mostly unaware of his rights. Against this backdrop, the authors intended to evaluate the working of the District Consumer Forum (DCF), Kadapa in terms of safeguarding the interests of the consumers from the unscrupulous business practices.